SMART-EDUCATION AS A FACTOR OF INDEPENDENT WORK - Khurshida Pardaeva (International Scientific and Current Research Conferences, 2024)
The article examines SMART-education as a factor in the implementation of students' independent work in credit-module conditions , as well as analyzing and defining the main concepts of SMART education and showing the relationship between these concepts. Three important aspects of SMART education are highlighted: organizational, technological and pedagogical. The concept of SMART education is currently associated with a number of concepts, many of which do not have the same interpretation. The first pedagogical component of the SMART education structure is SMART education, which consists of 2 different systems: SMART environment; SMART University. A SMART environment can be formed inside and outside the university, we focus on the SMART environment that manifests itself within the university. SMART University consists of three parts: SMART-campus , SMART-teachers , SMART-students. Since all three components are SMART, they must meet strict requirements. Formation of students' ability to work independently is one of the important requirements of SMART education. The SMART education concept is aimed at providing the highest level of knowledge and skills, allowing graduates to prepare competitive specialists, primarily for higher education institutions.